Slow pyrolysis of waste navel orange peels with metal oxide catalysts to produce high-grade bio-oil - Zhang Wei; Xia Hongying; Deng Yong; Zhang Qi; Xin Chunfu (Green Processing and Synthesis, 2022)
Renewable biomass resources have become increasingly attractive in recent years. In this study, the pyrolysis of waste navel orange peels was carried out with different metal oxides (Cu2O, CaO, V2O5, Fe2O3, and ZnO) in a tube furnace to obtain high-quality bio-oil, from which high-value chemicals such as 3-furaldehyde could be well recovered to enhance the economic value of waste navel orange peels. The effects of different metal oxides on bio-oil were analyzed by GC/MS. The results showed that Cu2O and Fe2O3, as catalysts for slow pyrolysis, promoted the production of 3-furaldehyde compounds at a scale of approximately 5.69 and 4.82 times higher than that of pyrolysis without the addition of metal oxides, respectively. High-value chemicals such as 3-furaldehyde obtained from bio-oil can enhance the economic value of waste navel orange peels for full recovery and reuse.